Modernes Netzwerken: thematische Ausrichtungen in der Arbeitsgruppe „Blasenkarzinom Experimentell“ der GeSRU Academics - Hofbauer, Sebastian; Worst, Thomas (Der Urologe, 2017)
In January 2015, the research group “bladder cancer research” was founded as part of the GeSRU Academics research initiative. A general challenge to work successfully in a novel network structure is to identify common scientific topics and technical expertise in the group. Thus, one of the first tasks was to learn about current research projects from members within the group in order to address a project that suits the group’s expertise. The following review summarizes three different directions that are key projects in Urologic Departments at German Universities that will be the basis to start fruitful collaborations.